FAKTOR-FAKTOR FUNDAMENTAL YANG MEMPENGARUHI RETURN SAHAM DAN DAMPAKNYA TERHADAP FREKUENSI PERDAGANGAN SAHAM SEKTOR INDUSTRI BARANG KONSUMSI PADA BEI TAHUN 2010-2017 - Anggraeni, Devina Putri; Salim, M Noor (BISMA: Jurnal Bisnis dan Manajemen, 2019)
This study aims to examine and analyze the fundamental factors represented by financial ratios, i.e., Return on Assets (ROA) which represents the profitability ratio; Debt to Equity Ratio (DER) which represents the solvency ratio; Current Ratio (CR) which represents the liquidity ratio; and Total Asset Turn Over (TATO) which represents the activity ratio, in its effect on stock returns and their impact on the frequency of stock trading. The research data was taken from the companies of the consumer goods sector listed on the Indonesia Stock Exchange in 2010-2017. The sampling method used was purposive sampling. Of the total population of 41 companies, 21 companies were used as research sample. The analytical method used was panel data analysis run by Eviews 9. The results showed that ROA affects stock returns, while DER, CR, and TATO do not affect stock returns. ROA, DER, CR, and TATO simultaneously affect the frequency of stock trading. However, only TATO has a partial effect on the frequency of stock trading, while stock returns do not affect the frequency of stock trading.